A SWOT analysis of the financial decentralization strategies for the Romanian pre-university education - Emilian-Constantin Miricescu; Lucian Ţâţu (Romanian Journal of Fiscal Policy (RJFP), 2014)
The paper focuses on Romanian experiences regarding the financial strategies used by managers from pre-university education. In Romania, local public authorities provide funds to pre-university institutions. Given the sharp economic recession and the austerity measures imposed by Romanian government, the public executives had to find solutions in collecting additional funds and in spending wisely the existing financial resources. Therefore, our paper aims at examining several practices regarding: (i) employees' wages, (ii) EU funds implementing, (iii) self-financing activities, (iv) public procurement and (v) balancing strategies for the budgets, which could improve the financial management of public institutions. This also can contribute to the increase in the efficiency of spending at micro-level within public administration.
Keywords: I22; H41; H75; 330; Decentralization strategy; Pre-university education; EU funds; SWOT analysis